EFEKTIVITAS PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) DALAM MENINGKATKAN PENYESUAIAN SOSIAL ANAK ASUH DI PANTI ASUHAN WIRA LISNA PADANG - Khaira, Imalatul; Firman, Firman; S, Neviyarni (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
The social adjustment as a process of adjustment to takes place in a sustainable. In their life, a person will be confronted with two realities that is self and their surroundings. Foster children that break the rules of orphanage, irresponsible, and unable to communicate well is indicative of the low social adjustment. REBT looked that the inability of individuals in interpersonal relationship resulting from irrational thinking. One of the efforts made to improve social adjustment is by doing REBT approach.Â  This research was aimed at revealing the effectiveness of REBT approach in improving foster care social adjustment. This research is a One Group Pretest-Posttest Design. By using Simple Random Sampling technique. The class consisted of 10 students the treatment was given in 6 meetings. The instrument was a scale model of Likert. Data were analyzed by using Wilcoxon Signed Ranks Test assisted with SPSS versi 20.00. The result indicates that, in general, REBT approach Setting Group was effective in improving the social adjustment of foster children in orphanages Wira Lisna Padang. Meanwhile, in particular, there was a significant differences in the average scores between the social adjustment foster children before and after doing REBT approach Setting Group.